Neuroprotective and antioxidant activities of Colombian plants against paraquat and C2-ceramide exposure in SH-SY5Y cells - Bustos-Rangel, Angie; Muñoz-Cabrera, Jonathan; Cuca, Luis; Arboleda, Gonzalo; Ávila Murillo, Mónica; Sandoval-Hernández, Adrián G. (Frontiers in Natural Products, 2023)
Abnormal production of reactive oxygen species (ROS) has been implicated in the physiopathology of neuronal cell death. Increased ROS levels are associated with exacerbated peptide aggregation, inflammation, and mitochondrial dysfunction, which facilitate the triggering of specific cell death pathways. Antioxidant molecules are potentially useful in the amelioration of neurodegeneration. In this regard, natural products are an invaluable source of antioxidants. Therefore, we investigate the antioxidant and neuroprotective activities of four Colombian angiosperm extracts. Antioxidant activity was evaluated by phytochemical assays using TLC techniques with Dragendorff reagent, ninhydrin, and chloranil in dioxane, NH3, Fast Blue, and FeCl3, together with bioautography using DPPH and β-carotene. In vitro neuroprotective activity, cell death, and ROS accumulation were evaluated by MTT and flow cytometry in the SH-SY5Y cell line exposed to paraquat and C2-ceramide. We found that Zanthoxylum rhoifolium Lam, Zanthoxylum martinicense, Nectandra membranacea, and Nectandra reticulata extracts have antioxidant activity higher than quercetin under a β-carotene bleaching assay and protect SH-SY5Y cells against paraquat and C2-ceramide associated with a reduction in ROS. In conclusion, these extracts have a strong neuroprotective potential, and the precise mechanism requires more evaluation.